Home Sweet Home: Working from home and employee performance during the COVID-19 pandemic in the UK - Sumit S. Deole; Max Deter; Yue Huang (Global Labor Organization (GLO), 2021)
In 2020, the COVID-19 pandemic forced governments in many countries to ask employees to work from home (WFH) where possible. Using representative data from the UK, we show that increases in WFH frequency are associated with a higher self-perceived productivity per hour and an increase in weekly working hours among the employed. The WFH-productivity relationship is stronger for employees residing in regions worse affected by the pandemic and those who previously commuted longer distances, while it is weaker for mothers with childcare responsibilities. Also, we find that employees with higher autonomy over job tasks and work hours and those with childcare responsibilities worked longer hours when working from home. With prospects that WFH possibility may remain permanently open for some employees, we discuss our results' labor market policy implications.
Keywords: J22; J24; 330; Working from home; productivity; working hours; COVID-19 pandemic